Agroindustry innovation: components, trends and challenges. - Arce Quesada, Silvia (2019)
The research aimed to generate a conceptual framework on the most relevant and updated topics of innovation in agribusiness. The methodology was based on a systematic search for information that initially allowed to form a conceptual framework on innovation in agribusiness, until identifying the components, trends and different actions in the agribusiness sector. The concept of innovation published in the Oslo Manual (2005), which is a guide for carrying out measurements and studies of scientific and technological activities, was considered as a reference for this research. Other instances such as the Inter-American Institute for Cooperation on Agriculture (IICA), refer to the concept of innovation as "change, explore, generate value, reinvent" (IICA, 2011). Diversification of definitions for the term innovation is evidenced, and it is precisely this fact that makes many of the studies on innovative companies not comparable, for this reason, the definition of innovation has required to be redefined, due to its interpretable character and not very precise (Cornell, 2018). It is concluded that innovation in agribusiness is enhanced by its involvement in dynamics mainly led by Agroindustry 4.0, Biotechnology and Bioeconomy